AMÈN: Tatakelola Wayang Jekdong dalam Tradisi Jawa Timuran - WISMA NUGRAHA CHRISTANTO (Institut Seni Indonesia Yogyakarta, 2008)
Amen: Jekdong Shadow Puppet Play Management in East Java Tradition. Amen is a moving jekdongshadow puppet performances from one place to another place. This is done by a cantrik ( puppet master assistant)in his last period of study. This is a kind of procession preparing a puppet master assistant to meet any possibilitiesand challenges in different kinds of situations for his future shadow puppet performances. Amen is a better wayfor a puppet master assistant to know and compete in the markets of shadow puppet business. Furthermore, amenis also done by a dalang ( puppet master) together with some panjak (musicians) in rainy season when farmers startto cultivate their rice fi elds. Since it is not the time for harvest yet and not the time for them to do some traditionalceremonies and rituals, amen becomes a way of